Resolving Conflicts of Frodo Baggins in J.R.R Tolkien’s The Fellowship of The Ring - Andriana, Febrian Dwi (English Literature Study Program, 2022)
This research aimed to analyze the interactions and reactions of Frodo Baggins as he faced some inner conflict. The researcher used Kurt Lewin's theory and Johnson’s theory in analyzing the inner conflicts that Frodo experienced. The researcher used the psychological approach to know the forms of inner conflict of Frodo experience and how Frodo resolves the inner conflict in J.R.R Tolkien’s novel entitled The Lord of The Ring: The Fellowship of The Ring. The results found that in analyzing inner conflict used Kurt Lewin's theory, there are three types of inner conflict experienced by Frodo Baggins in the novel The Lord of The Ring: The Fellowship of the Ring. The researcher found three form of inner conflict, there are: (1) Approach-Approach Inner Conflict had 3 data 2) Avoidance-Avoidance Inner Conflict had 10 data 3) Approach-Avoidance Inner Conflict had 8 data. The second research question used the Johnson’s theory that Frodo Baggins resolves his inner conflict in the novel The Lord of The Ring: The Fellowship of the Ring. The researcher found 5 styles to resolve inner conflict: (1) Turtle style has 1 data, (2) Shark style has 2 data, (3) Mouse deer style has 5 data, (4) Fox style has 2 data, and (5) Owl style has 2 data. It can be concluded the Avoidance-Avoidance Inner Conflict and the Mouse deer style is the most frequently happened to Frodo Baggins.